Public policy considerations arising from the exchange of information about South African taxpayers with countries that sanction the use of death penalty, with a focus on China - Els, Karla (Department of Commercial Law, 2020)
The paper evaluates how South Africa’s public policy towards the death penalty is protected amidst increased taxpayer information transparency. The People’s Republic of China (China) may, under article 22(4) of the Joint Council of Europe/OECD Convention on Mutual Administrative Assistance in Tax Matters (2010) (Multilateral Convention), use information received from South Africa, for criminal prosecution of a South African taxpayer in a non-tax matter in China, if the South African Revenue Service (the SARS) authorises such use. The Criminal Law of the People’s Republic of China 86 of 1997 sanctions the use of the death penalty for various economic crimes and this law has an unlimited territorial scope. China may therefore impose the death penalty on a South African taxpayer at the hands of information supplied by the SARS. This study will establish what public policy-based remedies are available for a South African taxpayer in this scenario. The SARS is not obliged to exchange information with China’s tax authority, as such an action will be contrary to South Africa’s public policy. Where the South African taxpayer concerned is in South Africa, including at a sea- or airport, then the SARS has a constitutional obligation not to exchange the information. Further, the South African state has an international obligation not to exchange the information where the method of execution in China is cruel, inhuman or degrading. The paper concludes that before exchanging the information and authorising its use for non-tax purposes, the SARS must take reasonable steps to evaluate whether it is foreseeable that the exchange of taxpayer information will be against South Africa’s public policy. The SARS is under a legal duty not to exchange information with China where the SARS foresees that such an action may lead to the imposition of the death penalty on a South African taxpayer in China. A further recommendation is that the public policy protection must be reinforced by amending the wording of the Multilateral Convention and the bilateral income tax treaty between China and South Africa in line with what other countries have done, in order to clarify that South Africa’s public policy specifically prevents the imposition of the death penalty.